Prevention of falls in the elderly: A review. Issue 5 (July 2013) - Karlsson, Magnus K.; Vonschewelov, Thord; Karlsson, Caroline; Cöster, Maria; Rosengen, Björn E.
Aims : Falls often result in soft tissue injuries, dislocations, fractures, longstanding pain and reduced quality of life. Therefore, fall preventive programmes have been developed. Methods : In this review, we evaluate programmes that in randomized controlled trials (RCT) have been shown with fall reducing effect. Results : Physical exercise that includes several training modalities, especially balance and strength training, is the only intervention programme that reduces both the number of fallers and the number of falls in community dwellers. Home hazards modification reduces the fall risk in community-living elderly but has the best effects in high risk groups when the programme is led by occupational therapists. Vitamin D supplement in those with low levels of vitamin D, adjustment of psychotropic medication and modification of multi-pharmacy are drug-related programmes that reduce the fall risk. Anti-slip shoe devices in elderly who walk outdoors during icy conditions and multifaceted podiatry to patients with specific foot disability are interventions targeted at the lower extremities with a fall-reducing effect. First eye cataract surgery and pacemakers in patients with cardio-inhibitory carotid sinus hypersensitivity are surgical procedures with fall-reducing effect. Multifactorial standardized preventive programmes that include an exercise component and individually-designed subject-specific programmes also reduce the number of falls. Conclusions : Fall preventive interventions should be provided to elderly by a structured approach, especially to high risk groups, as to reduce the number of falls and fallers.